Global trends in research of nasopharyngeal carcinoma: a bibliometric and visualization analysis - An, Guilin; Liu, Jie; Lin, Ting; He, Lan; He, Yingchun (Frontiers in Oncology, 2024)
Objective This study aims to assess the current research status, focus areas, and developmental trends in nasopharyngeal carcinoma (NPC) through a bibliometric analysis. Methods Articles focusing on NPC published from 2000 to 2023 were retrieved from the Web of Science database. VOSviewer and CiteSpace were used for bibliometric and visual analysis. Results A total of 14516 related publications were retrieved. There has been a steady increase in the number of NPC-related publications from 2000 to 2023. China was the dominant country in this field with 8948 papers (61.64%), followed by the USA (2234, 15.39%). Sun Yat-sen University was the most influential institution, while Ma J was the most prolific author. Furthermore, Head And Neck-journal For The Sciences And Specialties Of The Head And Neck was the most prolific journal. International Journal of Radiation Oncology Biology Physics had the highest total citation counts. "Introduction chemotherapy", "Concurrent chemotherapy", "Epithelial-mesenchymal transition", "Cancer stem cells", "MicroRNAs", "LncRNA", "Exosomes", and "Biomarker" were the most common keywords. The reference "Chen YP, 2019, Lancet" had the highest citations and strong outbreak value. Conclusion The past two decades have witnessed a significant increase in research on NPC. The optimization of treatment mode is the most widely studied aspect at present. The mechanism of occurrence and development and the most favorable diagnostic and therapeutic targets are the research hotspots in the future.